COMPARATIVE EVALUATION OF CONSUMER PROPERTIES OF SPECIAL DEER CUTLETS AND CUTLETS DEVELOPED ACCORDING TO THE TRADITIONAL RECIPE AND TECHNOLOGY - I. A. Zachesova; S. V. Kolobov (Современная наука и инновации, 2022)
The article presents the results of the comparative evaluation of consumer properties of particular Deer chops and cutlets, produced according to traditional recipes and technologies determined that Deer burgers special organoleptic characteristics are not inferior to the control sample. Amino acid composition of protein cutlets without Jerusalem artichoke powder and special cutlets Is close to the reference value of FAO/who. When adding powder from Jerusalem artichoke tubers in cutlets, the content of vitamins B1, B2, B5, C Increases, and vitamin B7, which is not found in the control sample, is also found. In deer cutlets special higher content of calcium, potassium, iron, and contains silicon, which is not in the control sample cutlets. Studies have shown that special deer cutlets have high consumer properties.